Hubungan Tingkat Kecemasan Ibu Menyusui dengan Kelancaran Pengeluaran ASI di Masa Pandemi Covid-19 - Putu Mas Saraswati; Ni Nyoman Hartati; Suratiah Suratiah; Nengah Runiari (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2023)
Feelings of anxiety can affect the release of breast milk which causes milk to come out late. The COVID-19 pandemic has caused high anxiety disorders in the Indonesian population which can affect the smooth release of breast milk. This study aimed to determine the relationship between the anxiety level of mothers during breastfeeding 0-2 years and the smoothness of expressing breast milk during the COVID-19 pandemic in the UPT work area. Ubud Public Health I uses a correlational research design that aims to reveal the correlative relationship between variables with a cross-sectional approach. Sampling uses nonprobability sampling with purposive sampling technique. The number of samples used in the study were 105 samples. The instruments used in this study were anxiety questionnaires for breastfeeding mothers and the smoothness of breastfeeding. The analysis technique used to see the relationship between the two variables is the Spearman rank test. The results of the study found that the anxiety level of the majority of breastfeeding mothers was moderate by 40 people (38.1%), and 48 people (45,7%) experienced irregular breastfeeding. Statistical test using Spearman rank obtained p value = 0.00 alpha (0,05) It can be concluded that there is a significant relationship between the anxiety level of mothers during breastfeeding 0-2 years and the smoothness of breastfeeding during the COVID-19 pandemic in the UPT work area. Public Health of Ubud I. It is suggested to the government that there should be a health service program related to efforts to deal with the impact of the COVID-19 pandemic on people's mental health.